Impact of AI Technologies on Teaching, Learning, and Research in Higher Education - Ojha, Dharma Raj (Journal of Jayaprithvi Multiple Campus, 2025)
The higher education sector is experiencing a rapid influx of artificial intelligence, which is resulting in significant improvements in administrative processes, efficacious instruction, and personalized learning. This paper investigates the potential of Artificial Intelligence (AI) technologies, including adaptive learning platforms, to personalize learning experiences for students, automate repetitive duties, and provide educators with valuable insights. The discussion centers on the ways in which artificial intelligence technologies are being utilized to customize learning, automate administrative activities, and improve decision-making that is driven by data. Through data analytics, artificial intelligence has delivered real-time insights, dramatically improved tailored learning experiences, and automated administrative procedures such as scheduling and grading. Despite this, there are still significant problems to be solved, such as algorithmic bias and data privacy. AI in education has the potential to improve student learning outcomes, increase instructional effectiveness, and allocate resources more efficiently. To optimize the advantages of AI, educators and students must develop digital literacy and ethical concerns. In order to investigate the practical applications of AI in a variety of educational environments, future research should involve more extensive, quantitative studies.